PERAN PARA PIHAK DALAM PENANGANAN KONFLIK DI KESATUAN PENGELOLAAN HUTAN PRODUKSI DELTA MAHAKAM, KALIMANTAN TIMUR - Surati Surati; Sylviani Sylviani (Jurnal Analisis Kebijakan Kehutanan, 2016)
Delta Mahakamregion has high economic and conservation value, making the management ofthis region facing considerable challenge. Government intervention is required in order to create management that takes into account the ecological value of this region. Potential conflicts occurred among stakeholders in this region The aim of the study was to identify the role of. stakeholders, the explanation of conflict of interest, potential and influence in conflict in the forest area ofresolution Delta Mahakam was done by using PIL (Power, Interest, Legitimacy) analytical method, to evaluate roles of. The analysis techniqueeach stakeholders in the . The results showed that the potential conflicts among stakeholders in the conflict resolution Production Forest Management Unit (PFMU/KPHP) Delta of Mahakam could be grouped into: central government, local government, NGOs and academia, oil and gas companies, fishermen, plantation and mining companies, as well as forest communities Potential conflicts may . occur bilaterally or alliance, which involved the owners of interest (central government, local government, society) withthe positiveiowner ofve (oil and gas company, with fishermen). Understanding of each  stakeholder on their respective roles were very negatif interest important for the sustainable management of that region.